Systematic Literature Review: Nurses' Work Hours and Workload Impact on Patient Safety Incidents - Edi Kurnawan; Farida Yuliaty (Jurnal Indonesia Sosial Sains, 2024)
Patient safety is a key indicator in assessing the quality of healthcare services in hospitals, and nurses play a crucial role in maintaining that safety. However, long working hours and high workloads can affect nurses' performance, increasing the risk of fatigue, stress, and burnout, ultimately contributing to medical errors and decreased quality of care. This study aims to conduct a systematic literature review on the effect of nurses' working hours and workload on hospital patient safety incidents. Patient safety is a key indicator in assessing healthcare quality, and nurses play an essential role in maintaining patient safety during daily care. However, long working hours and high workloads can affect nurses' performance, increasing the risk of fatigue, stress, and burnout, ultimately contributing to medical errors and decreased quality of care. Through the analysis of various relevant studies, this review suggests that more flexible working hour arrangements and balanced workload management can reduce the risk of patient safety incidents and improve the quality of care provided. This study also recommends that hospital human resource management to create a healthier and safer working environment for nurses and patients.